A return to the Qur'anic paradigm of development and integrated knowledge: The Ulu al-Albab model - Hassan, Mohd. Kamal (IIUM Press, 2010)
The paper highlights that the secular and modernistic paradigm of development that lacks spiritual and ethical moorings is partly responsible for the 2009 global economic and financial crisis. Muslim policy-makers, intellectuals and scholars are duty-bound to promote the Tawhidic paradigm of holistic development and holistic knowledge. Closely related to the paradigm of development is the issue of the epistemology of autonomous human reason which denies the importance and validity of Divine revelation as a higher source of knowledge and wisdom. The Quran projects the model of the Ulu al-Albab, people of sound reason as intellectuals and scholars par excellence who combine the understanding of the Book of Nature with the Book of Revelation, and integrate human reason with Divine revelation. The paper ends by suggesting that Muslim countries develop institutions of learning or systems of education which integrates worldly knowledge with religious knowledge in a harmonious and symbiotic manner.